Efektivitas Pembelajaran Daring pada Mata Pelajaran IPA di Masa Pandemi Covid-19: Studi Komparasi Pembelajaran Luring dan Daring pada Mata Pelajaran IPA SMP - Anita Ekantini (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2020)
The Covid-19 pandemic affects all areas of life, including education. The Covid-19 pandemic prompted the government to issue a distance learning policy. Online learning is one of solution to solve this problem. The objectives of this study were: (1) to compare the differences in science learning outcomes between offline learning and online learning, and (2) to determine the effectiveness of online science learning during the Covid-19 pandemic. This research is a quasi-experimental study using the comparative method. Science learning outcomes before the Covid-19 pandemic (offline) were compared with science learning outcomes during the Covid-19 pandemic (online). The findings of this research were (1) there were differences in students 'science learning outcomes in offline learning with students' science learning outcomes in online learning, and (2) offline science learning was more effective than online science learning.